Is Reasoning a Fruitful Path to Changing Minds?. Issue 1 (2nd January 2020) - Kuhn, Deanna; Cummings, Amy; Youmans, Michael
ABSTRACT: The thinking underlying people's positions on complex issues is often of limited scope or complexity, yet changing minds is notoriously difficult. We investigated the thinking underlying people's positions on the Deferred Action for Childhood Arrivals program. Rather than seek to influence their thinking by engaging them in considering alternative views, we investigated the effectiveness of engaging them in discourse by asking them to explore limitations, inconsistencies, and unresolved issues with respect to their own positions. Might doing so enrich their thinking about the issue? This hypothesis was disconfirmed, showing to the contrary that the intervention prompted endorsement of more extreme views consistent with one's own position. Individual difference findings showed more complex, comprehensive thinking supporting a position (justifications included multiple dimensions or considerations) to be associated with less extreme positions and lower reported affect. Implications are considered for public opinion assessment and for promoting thoughtful positions on complex issues.